Postal services in the digital age - Finger, Matthias; Bukovc, Bernhard; Burhan, Muqbil (Global e-governance series, 2014)
In recent years, the postal sector has undergone radical changes, which have primarily been driven by operational and technological developments. Not only has the advent of Information and Communication Technology (ICT) added competition to the market, but it has also provided ample opportunity for the broadening and improvement of services and product range. This book deals with the challenges faced by the postal sector in the digital age, and with the vast opportunities that technological advancements offer postal operators with regard to developing new business solutions and services tailore.